Comparing the pooled cohort equations and coronary artery calcium scores in a symptomatic mixed Asian cohort - Baskaran, Lohendran; Lee, Jing Kai; Ko, Michelle Shi Min; Al’Aref, Subhi J.; Neo, Yu Pei; Ho, Jien Sze; Huang, Weiting; Yoon, Yeonyee Elizabeth; Han, Donghee; Nakanishi, Rine; Tan, Swee Yaw; Al-Mallah, Mouaz; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The value of pooled cohort equations (PCE) as a predictor of major adverse cardiovascular events (MACE) is poorly established among symptomatic patients. Coronary artery calcium (CAC) assessment further improves risk prediction, but non-Western studies are lacking. This study aims to compare PCE and CAC scores within a symptomatic mixed Asian cohort, and to evaluate the incremental value of CAC in predicting MACE, as well as in subgroups based on statin use. Methods Consecutive patients with stable chest pain who underwent cardiac computed tomography were recruited. Logistic regression was performed to determine the association between risk factors and MACE. Cohort and statin-use subgroup comparisons were done for PCE against Agatston score in predicting MACE. Results Of 501 patients included, mean (SD) age was 53.7 (10.8) years, mean follow-up period was 4.64 (0.66) years, 43.5% were female, 48.3% used statins, and 50.0% had no CAC. MI occurred in 8 subjects while 9 subjects underwent revascularization. In the general cohort, age, presence of CAC, and ln(Volume) (OR = 1.05, 7.95, and 1.44 respectively) as well as age and PCE score for the CAC=0 subgroup (OR = 1.16 and 2.24 respectively), were significantly associated with MACE. None of the risk factors were significantly associated with MACE in the CAC>0 subgroup. Overall, the PCE, Agatston, and their combination obtained an area under the receiver operating characteristic curve (AUC) of 0.501, 0.662, and 0.661 respectively. Separately, the AUC of PCE, Agatston, and their combination for statin non-users were 0.679, 0.753, and 0.734, while that for statin-users were 0.585, 0.615, and 0.631 respectively. Only the performance of PCE alone was statistically significant (p = 0.025) when compared between statin-users (0.507) and non-users (0.783). Conclusions In a symptomatic mixed Asian cohort, age, presence of CAC, and ln(Volume) were independently associated with MACE for the overall subgroup, age and PCE score for the CAC=0 subgroup, and no risk factor for the CAC>0 subgroup. Whilst the PCE performance deteriorated in statin versus non-statin users, the Agatston score performed consistently in both groups.